Structural Behavior of Reinforced Concrete Hollow Core Slabs Cast with Self-Compacting Concrete Containing Recycled Concrete as Coarse Aggregate - Hassan, Mustafa Raheem; Khudhair, Jamal Abdulsamad (Basrah Journal for Engineering Sciences, 2023)
This paper investigates the possibility of recycled aggregate use in concrete slabs with hollow cores. The main variables considered in the experimental study for the slabs were the recycled aggregate percentage and the hollow core number. Six slabs with dimensions of (1000 × 500 × 120) mm was fabricated and tested. The results showed that the addition of recycled aggregate in the concrete slabs affected the ultimate strength, ductility, and energy absorption of the concrete members. An increase of the recycled aggregate percentage to 25 % decreased the ultimate strength capacity by 3.54 %, but the increase of recycled aggregate to 50 % led to a decrease in the ultimate strength of about 6.64%. The existence of a hollow core reduced the cracking and ultimate load capacity of the RCA slabs, and this reduction was according to the core number which the fabrication of more cores caused more decrement. The ductility and energy absorption were decreased when the replacement ratio of the recycled aggregate increased. Also, the core number affected the ductility and energy absorption. The energy absorption was the most property affected by the core number increase which caused an average reduction of 71.5 % when the core number increased from two to three hollow cores.